Upper and Lower Almost Contra-$(τ_1,τ_2)$-continuity (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces new classes of multifunctions between bitopological spaces, namely upper almost contra-$(τ_1,τ_2)$-continuous multifunctions and lower almost contra-$(τ_1,τ_2)$-continuous multifunctions. Furthermore, several characterizations of upper almost contra-$(τ_1,τ_2)$-continuous multifunctions and lower almost contra-$(τ_1,τ_2)$-continuous multifunctions are considered.
Keywords: upper almost contra-$(τ_1,τ_2)$-continuous multifunction; lower almost contra-$(τ_1,τ_2)$-continuous multifunction